Regulation of the Bone Marrow Niche by Inflammation - Mitroulis, Ioannis; Kalafati, Lydia; Bornhäuser, Martin; Hajishengallis, George; Chavakis, Triantafyllos (Frontiers in Immunology, 2020)
Hematopoietic stem cells (HSC) reside in the bone marrow (BM) within a specialized micro-environment, the HSC niche, which comprises several cellular constituents; these include cells of mesenchymal origin, endothelial cells and HSC progeny, such as megakaryocytes and macrophages. The BM niche and its cell populations ensure the functional preservation of HSCs. During infection or systemic inflammation, HSCs adapt to and respond directly to inflammatory stimuli, such as pathogen-derived signals and elicited cytokines, in a process termed emergency myelopoiesis that includes HSC activation, expansion and enhanced myeloid differentiation. The cell populations of the niche participate in the regulation of emergency myelopoiesis, for instance, through secretion of paracrine factors in response to pro-inflammatory stimuli, thereby indirectly affecting HSC function. Here, we review the crosstalk between HSCs and cell populations in the BM niche, specifically focusing on the adaptation of the HSC niche to inflammation and how this inflammatory adaptation in turn may regulate emergency myelopoiesis.